A 6-week, multicenter, double-blind, double-dummy, chlorpromazine-controlled non-inferiorityrandomized phase iiitrial to evaluate the efficacy and safety of quetiapine fumarate (SEROQUEL) extended-release (XR) in the treatment of patients with schizophrenia and acute episodes. (January 2018) - Li, Huafang; Shen, Yifeng; Wang, Gang; Shi, Jianguo; Ma, Cui; Xie, Shiping; Zhang, Honggeng; Wang, Xiaoping; Li, Keqing; Xu, Xiufeng; Gu, Niufan
Abstract: This study aimed to evaluate the efficacy and safety of quetiapine fumarate extended-release (XR) in the treatment of Chinese patients with acute schizophrenia. Multicenter, double-blind, double-dummy, active-controlled non-inferiority randomized study in Chinese patients (n = 388) with schizophrenia randomly assigned to quetiapine XR or chlorpromazine for 6 weeks. Primary outcome was the change from baseline in Positive and Negative Syndrome Scale (PANSS) total score at the end of treatment. Safety objectives included adverse event (AE) monitoring, laboratory test results, and electrocardiograms. Changes in PANSS total score were −33.4 for quetiapine XR and −35.9 for chlorpromazine (P > 0.05). Least squares mean changes were: positive subscale, −9.9 ± 0.53 and −11.1 ± 0.51; negative subscale, −5.9 ± 0.50 and −6.7 ± 0.48; general psychopathology subscale, −12.9 ± 0.74 and −13.9 ± 0.71; aggression and hostility cluster scores, −4.8 ± 0.33 and −5.4 ± 0.32; and depression cluster scores, −1.8 ± 0.18 and −1.7 ± 0.18, for quetiapine XR and chlorpromazine, respectively. For quetiapine XR, AEs were constipation, dizziness, insomnia, and agitation, and nine patients (4.6%) discontinued due to AEs. For chlorpromazine, AEs were extrapyramidal symptoms, constipation, insomnia, dizziness, and agitation, and 17 patients (8.9%) discontinued due to AEs; two patients reported serious AEs. Quetiapine XR monotherapy was not inferior to chlorpromazine for treating acute schizophrenia in Chinese patients and was well tolerated. Highlights: Quetiapine XR monotherapy is not inferior to chlorpromazine to treat schizophrenic patients. Quetiapine XR monotherapy shows a positive risk benefit ratio. Quetiapine XR monotherapy is generally safe and well tolerated.